The Power of Story Face Strategy and Concept Mapping Strategy in Teaching Students’ Reading Skill - Hamid Ismail; Saiful Saiful; Rina Asrini Bakri (AL-ISHLAH: Jurnal Pendidikan, 2022)
The goal of this study is to determine the relationship between independent and dependent variables. To investigate the impact of the story face strategy and the concept mapping strategy on second grade students' reading comprehension at senior high school. This is an experimental study with a pre test and post test design. The research sample consisted of second grade students (2 Sains classes) during the academic year 2018/2019, and the purposive sampling technique was used. The effect of Story Face Strategy and Concept Mapping Strategy toward reading comprehension based on the data indicates that there was significant effect between data in pre-test and data taken from post-test of the students' achievement. The value of the test was highly significant showed as 19.088 and the t-table was showed as 2.093. The value score of t-test was quite higher than the t-table (19.088 2.093). It is concluded that the Story Face Strategy and Concept Mapping Strategy are effective in teaching reading skill to senior high school second grade students.